Adjustable dual temperature-sensitive hydrogel based on a self-assembly cross-linking strategy with highly stretchable and healable properties. Issue 4 (4th March 2021) - Ge, Sijia; Li, Jiajia; Geng, Jian; Liu, Shinian; Xu, Hua; Gu, Zhongze
Abstract : A novel PNIPAm/PNAGA double-network hydrogel based on a self-assembly cross-linking strategy was prepared for the first time. Due to the existence of various hydrogen bonds, the hydrogel exhibits a wide and adjustable dual temperature-sensitive behavior of LCST-type and UCST-type, and highly stretchable, and healable properties, which indicated great potential applications in the simulation of human skin to monitor various ambient temperatures. Abstract : Developing smart temperature-sensitive hydrogels with a wide response range and highly stretchable and healable properties for simulation of the temperature perception function of human skin remains a great challenge. Here, a novel PNIPAm/PNAGA double-network hydrogel was developed by a self-assembly cross-linking strategy to achieve this goal. Benefiting from the double-network structure and a large number of multiple hydrogen bond interactions between the PNIPAm and PNAGA, the PNIPAm/PNAGA hydrogel realizes wide and adjustable dual temperature response behaviors of 0–32.5 °C (LCST) and 32.5–65 °C (UCST) and exhibits extraordinary mechanical properties with a maximum tensile strength of 51.48 kPa, elongation at break over 1400%, compressive stress over 1 MPa, and Young's modulus approximately 5.51 kPa, and excellent healable properties of nearly 100% temperature-sensitive repair rate. To the best of our knowledge, this is the highest mechanical strength of the reported PNIPNm-based dual temperature-sensitive hydrogels and simultaneously achieved the healable performance of dual temperature-sensitive hydrogels for the first time. The PNIPAm/PNAGA hydrogel displayed superior capability for simulation of the human skin to monitor various ambient temperatures, such as human skin temperature, hot and cold water, a refrigerator, room temperature and oven temperature, indicating promising applications in the fields of electronic skin, wearable device, bionics, etc.